A SHORT REVIEW OF URINARY SYMPTOMATOLOGY- GRECO ARAB MEDICINE - Rahman, Azizur; Zulkifle, Mohd; Khan, Mohammad Ruman; Aslam, Mohammad (Universal Journal of Pharmaceutical Research, 2020)
Greco Arab physicians have explained diseases as well as their signs and symptoms. They have documented the importance of urinary Symptomatology in diagnosis of disease and other conditions of body. They have classified the symptoms on the basis of time period, temporary or permanent etc. They discussed the factors affecting the urine presentation related to urinary tract condition. Symptomatology related to urine available in the Greco Arab classical books were being surveyed. After extensive review of literature, it was found that; Unani physicians were very much familiar to diseases of urinary tract and their signs and symptoms. Urine Symptomatology is very important aspect of medical science; every physician must know the presentation of diseases to make good differential diagnosis, right diagnosis and treatment. Peer Review History: Received 1 December 2019; Revised 12 January 2020; Accepted 25 February; Available online 15 March 2020 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Adebayo Gege Grace Iyabo , University of Ibadan, Nigeria, funbimbola@gmail.com Dr. George Zhu , Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com